2015
DOI: 10.4253/wjge.v7.i3.213
|View full text |Cite
|
Sign up to set email alerts
|

Endosonography in the diagnosis and management of pancreatic cysts

Abstract: Rapid advances in radiologic technology and increased cross-sectional imaging have led to a sharp rise in incidental discoveries of pancreatic cystic lesions. These cystic lesions include non-neoplastic cysts with no risk of malignancy, neoplastic non-mucinous serous cystadenomas with little or no risk of malignancy, as well as neoplastic mucinous cysts and solid pseudopapillary neoplasms both with varying risk of malignancy. Accurate diagnosis is imperative as management is guided by symptoms and risk of mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 81 publications
0
20
0
4
Order By: Relevance
“…Pancreatic cystic lesions (PCL) are discovered with increasing frequency as a result of the widespread use of high‐resolution cross‐sectional imaging techniques . At present, no single diagnostic tool has been found to be reliable for the differential diagnosis of PCL, and assessment of the risk of malignant transformation relies on information such as clinical history, results of radiological examinations, endoscopic ultrasound (EUS), cystic fluid analysis, and cytohistological testing …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cystic lesions (PCL) are discovered with increasing frequency as a result of the widespread use of high‐resolution cross‐sectional imaging techniques . At present, no single diagnostic tool has been found to be reliable for the differential diagnosis of PCL, and assessment of the risk of malignant transformation relies on information such as clinical history, results of radiological examinations, endoscopic ultrasound (EUS), cystic fluid analysis, and cytohistological testing …”
Section: Introductionmentioning
confidence: 99%
“…1,2 At present, no single diagnostic tool has been found to be reliable for the differential diagnosis of PCL, and assessment of the risk of malignant transformation relies on information such as clinical history, results of radiological examinations, endoscopic ultrasound (EUS), cystic fluid analysis, and cytohistological testing. 3,4 Radiological high-resolution cross-sectional imaging studies and EUS-morphology are usually not sufficient to accurately assess the need for surgery or surveillance, especially in cases of unilocular or oligocystic PCL. [4][5][6][7][8] Carcinoembryonic antigen (CEA) cystic fluid levels have limited accuracy and are not useful to confirm or rule out the presence of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…La tomografía es la prueba diagnóstica de elección, pues permite diferenciar los varios tipos de neoplasias quísticas con base en los siguientes criterios: localización, patrón intralesional (unilocular, oligoquístico, poliquístico), calcificaciones, comunicación con el conducto pancreático principal o los ductos laterales, septos y presencia de nódulos murales (13); sin embargo, en años recientes la ecografía endoscópica con o sin aspiración con aguja fina se ha afianzado como estrategia de estudio efectiva y segura en la clasificación de lesiones quísticas y sólidas del páncreas, que da información cuando el diagnóstico no es claro y confirma la presencia o ausencia de características de riesgo o el diagnóstico de malignidad (14,15).…”
Section: Discussionunclassified
“…Meticulous investigations showed that this case was not a PNET, and its final diagnosis after surgery was chronic pseudocyst that developed in chronic pancreatitis. Pseudocysts, retention cysts, lymphoepithelial cysts, and benign epithelial cysts are non-neoplastic cysts (26). When we grouped those lesions together, the mean CgA level was slightly higher in those groups compared with neoplastic cysts.…”
Section: Discussionmentioning
confidence: 99%